STRATEGI PENGEMBANGAN TANAMAN PANGAN DI WILAYAH AGROPOLITAN KECAMATAN KAWANGKOAN BARAT - Alfa S. Moniung; Juliana R. Mandei; Noortje M. Benu (COCOS, 2015)
ABSTRACT This study purpose is to determine the potential and development strategies in the area of food crops in agropolite region of West Kawangkoan District. This research was conducted for three months starting from April 2015 until June 2015 in West Kawangkoan District.  To determine the potential of food crops in in West Kawangkoan District was analyzed descriptively and to analyze the development strategy of food crops in the agropolitan region in West Kawangkoan District the writer’s using SWOT analysis. The results of the study showed that the agropolitan region in West Kawangkoan District has the potential for planting corn and peanuts because it is supported by a good land, good infrastructure of buildings, roads, transportation, market, electricity and telecommunications to support agricultural activities and also industry partnerships with other agencies for the development of agropolitan. The strategies for food crops development  in Western Kawangkoan  the farmers are to utilize the resources and skills in managing food crops of corn and peanuts, to increase productivity of food crops by using the appropriate technology, maximizing of the processing industry to meet the demand of consumers, to establish good cooperation with the Government in doing mentoring and monitoring of the distribution of seeds, fertilizer and  agricultural tools/machineries from manufacturer up to the diluent, merchants, to farmers in order to make available in a timely manner, as well as enhance cooperation between farmers with processing industry and animal feed industry results in developing regions of the western Kawangkoan as an agropolitan area. This region was selected based on the results from a SWOT analysis which was located in the first cell of second quandran is an aggressive strategy, this strategy can spur growth and development of food crops especially maize and peanuts in district Kawangkoan. Keyword : Food Crops and Agropolitan Regional